Mechanical stimuli induce cleavage and nuclear translocation of the polycystin-1 C terminus - Chauvet, Veronique (American Society for Clinical Investigation, 2004)
Polycystin-1, which is encoded by a gene that is mutated in autosomal dominant polycystic kidney disease (ADPKD), is involved in cell-matrix interactions as well as in ciliary signaling. The precise mechanisms by which it functions, however, remain unclear. Here we find that polycystin-1 undergoes a proteolytic cleavage that releases its C-terminal tail (CTT), which enters the nucleus and initiates signaling processes. The cleavage occurs in vivo in association with alterations in mechanical stimuli. Polycystin-2, the product of the second gene mutated in ADPKD, modulates the signaling properties of the polycystin-1 CTT. These data reveal a novel pathway by which polycystin-1 transmits messages directly to the nucleus.